Sakura Hime, the Legend of Princess Sakura 8 - Tanemura, Arina (Shojo Beat., 2012)
Enju and the followers of the moon are nowhere to be found after the distruction of the hidden palace. Sakura has returned with Aoba, but the lovers may soon be parted again. The emperor has asked Aoba to take another bride...